The research progress on synchronous endometrial and ovarian carcinoma - Gan, Wenli; Bian, Ce (Frontiers in Oncology, 2023)
Synchronous endometrial and ovarian carcinoma (SEOC) is the most common combination of primary double cancer in the female reproductive system. The etiology and pathogenesis of SEOC remain unclear, and clinically, it is often misdiagnosed as metastatic cancer, affecting the formulation of treatment plans and prognosis for patients. This article provides a review of its epidemiology, pathological and clinical characteristics, risk factors, pathogenesis, diagnosis, treatment, and prognosis.